Rejection and Recovery of Heavy Metals from MSW Melting Fly Ash by Carrier-in-Pulp Method - Alorro, Richard; Hiroyoshi, N.; Mitani, S.; Ito, M.; Tsunekawa, M. (Science Press, 2008)
Melting has become a popular pretreatment method for municipal solid waste (MSW) incineration residues in Japan. Although the method is effective in stabilizing the hazardous organic substances such as dioxin in the residue, it concentrates the heavy metals such as Zn, Pb, Cu, and Cd in a newly formed fly ash which is also known as melting fly ash. Melting fly ash is classified as a hazardous waste because of the leaching potential of these heavy metals in landfill environments. Extraction and recovery of these metals seem to be more environmentally and economically attractive than disposing the material to landfill after immobilization process. This study proposes a Carrier-in-Pulp (CIP) method as a new hydrometallurgical route to reject and recover heavy metals from fly ash before landfilling. In this method, a carrier material which recovers the extracted metals is added simultaneously with fly ash to leaching solutions and is harvested from the pulp by physical separation method like magnetic separation or sieving. To demonstrate the effect of CIP method, shaking flask experiments for melting fly ash were conducted under various conditions using NaCl solution as lixiviant and iron powder or granular activated carbon as carrier materials.In the CIP method using iron powder, more than 97 wt% of Pb, Zn, Cu, and Cd, were extracted from the ash to the solution phase. However, the iron powder which was harvested from the pulp by magnetic separation, recovered only Pb and Cu (more than 94%) through cementation, leaving behind Zn and Cd ions in the solution phase. Due to this problem, granular activated carbon was used as an alternative carrier material. The CIP method using activated carbon extracted more than 90% of Zn, Pb, Cu, and Cd from the ash. The carbon granules were separated from the pulp through sieving. The results showed that activated carbon was superior to the iron powder since it was able to recover the extracted heavy metals from the ash through adsorption. Around 70-95% of Pb, Zn, Cu, and Cd were recovered under various conditions. The leaching test conducted on the residue after the CIP treatment showed that the ash was successfully detoxified to meet the landfilling guidelines.